2012
DOI: 10.1038/ki.2012.115
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic prostaglandin E2–EP4 system of the renal tubular epithelium limits the development of tubulointerstitial fibrosis in mice

Abstract: Inflammatory responses in the kidney lead to tubulointerstitial fibrosis, a common feature of chronic kidney diseases. Here we examined the role of prostaglandin E(2) (PGE(2)) in the development of tubulointerstitial fibrosis. In the kidneys of wild-type mice, unilateral ureteral obstruction leads to progressive tubulointerstitial fibrosis with macrophage infiltration and myofibroblast proliferation. This was accompanied by an upregulation of COX-2 and PGE(2) receptor subtype EP(4) mRNAs. In the kidneys of EP(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 67 publications
2
91
0
Order By: Relevance
“…Indeed, it has recently been reported that PGE 2 /EP4 pathway has an antifibrosis effect in kidney interstitial cells. 43 In this study, we found that PGE 2 indirectly induced HSPC proliferation through the activation of MPCs. A more comprehensive understanding of these indirect effects of PGE 2 may facilitate the expansion of HSPCs for use in regenerative medicine.…”
Section: Ep4 Stimulation Increases Hspc Colony Formation and Ltr Capamentioning
confidence: 72%
“…Indeed, it has recently been reported that PGE 2 /EP4 pathway has an antifibrosis effect in kidney interstitial cells. 43 In this study, we found that PGE 2 indirectly induced HSPC proliferation through the activation of MPCs. A more comprehensive understanding of these indirect effects of PGE 2 may facilitate the expansion of HSPCs for use in regenerative medicine.…”
Section: Ep4 Stimulation Increases Hspc Colony Formation and Ltr Capamentioning
confidence: 72%
“…Culturing lung fibroblasts on stiff matrix, which activates adhesive signaling and is sufficient to trigger myofibroblast differentiation, has likewise been reported to down-regulate PGE 2 synthetic capacity (48). Deficient endogenous PGE 2 synthesis or actions promotes fibrogenesis, as evidenced by studies employing pharmacological interruption of PGE 2 synthesis (46, 49) and deletion of cAMP-coupled EP2 (50) and EP4 receptors (51). Taken together, this body of literature suggests that, rather than merely being of interest as an exogenously added substance, the suppressive actions of endogenous PGE 2 are so fundamental that tissue fibrogenesis can only occur when this potent antifibrotic brake is down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…8,12) Unilateral ureteral obstruction has been used to induce kidney fibrosis, and EP4 agonist mitigated interstitial fibrosis in this mouse model of chronic kidney disease. 21) These studies have indicated EP4 agonists have antifibrotic and organ protective effects. Pressure overload to the heart can cause acute myocardial injury and edema in acute phase, which is followed by the gradual development of fibrosis.…”
Section: Discussionmentioning
confidence: 99%